1987
DOI: 10.2337/diacare.10.1.68
|View full text |Cite
|
Sign up to set email alerts
|

No Glycemic Benefit From Guar Administration in NIDDM

Abstract: A randomized crossover study of 5-g guar minitablets against placebo, given three times per day with main meals for 8 wk, was done in 29 non-insulin-dependent diabetes mellitus (NIDDM) patients who had near-normal fasting plasma glucose concentrations on treatment with diet alone, additional sulfonylurea, or ultralente insulin. Guar did not reduce the excessive postprandial glycemic excursion, glycosylated hemoglobin values, basal plasma glucose concentrations, basal or incremental plasma C-peptide values, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Thus, Stahl and Berger (1990) found no significant differences in glycosilated haemoglobin after the administration of 15 g of guar gum daily during 3 months; Jones et al (1985), after the administration of 10 g=day during 2 months, obtained a significant fall in GhbA 1c levels, without significant changes in 24 h urinary glucose excretion. Behall (1990) observed that guar gum significantly reduced blood C-peptide concentrations after the administration of 31.7 g fibre per day during 6 months and Holman et al (1987) obtained no significant changes in blood C-peptide and GhbA 1c concentrations after the administration of 15 g=day during 8 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, Stahl and Berger (1990) found no significant differences in glycosilated haemoglobin after the administration of 15 g of guar gum daily during 3 months; Jones et al (1985), after the administration of 10 g=day during 2 months, obtained a significant fall in GhbA 1c levels, without significant changes in 24 h urinary glucose excretion. Behall (1990) observed that guar gum significantly reduced blood C-peptide concentrations after the administration of 31.7 g fibre per day during 6 months and Holman et al (1987) obtained no significant changes in blood C-peptide and GhbA 1c concentrations after the administration of 15 g=day during 8 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…Sometimes ®ber ingestion modestly improves glycaemic control (Carroll et al, 1981;Lim et al, 1990) or, although glucose tolerance is better, insulin response remains unchanged (Groop et al, 1993). In other studies the improvement of blood glucose, or decreased insulin requirements, in diabetic patients (Rivellese et al, 1980;Jones et al, 1985;Holman et al, 1987;Thomas et al, 1988;Sels et al, 1992;Groop et al, 1993) and enhanced glucose tolerance in healthy subjects could not be reproduced (Groop et al, 1986;Behall, 1990;Sels et al, 1992). These apparent discrepancies can be due to differences in dietary ®ber sources or in the composition of the diets employed, as well as to the interindividual variability in response (Chuang et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The efficacy of high fibre diets in the treatment of diabetes remains, controversial, [17][18][19] and, the use of purified fibre as a supplement is not advocated. 20 The present study was designed to assess the effect of a low GI diet, a high GI diet and a high fibre diet on glycaemic control and on premeal insulin requirement in well-controlled Type 1 diabetic patients on intensive insulin therapy.…”
Section: Introductionmentioning
confidence: 99%